DNA-based detection of pork content in food. Issue 3 (March 2023) - Muflihah,; Hardianto, Ari; Kusumaningtyas, Pintaka; Prabowo, Sulistyo; Hartati, Yeni Wahyuni
Abstract: Determination of halal food is essential in ensuring the tranquillity of consumers, especially Muslims. Halal products mean they are free from prohibited ingredients according to Islamic law. One ingredient that is prohibited is food products containing pork and its derivatives. An accurate verification method with a fast result is necessary to meet this requirement for halal food. DNA quantification of pork is now believed to be able to make accurate and quick decisions, as DNA acts as a reservoir or biological characterization of all living things, including pigs, according to specific characteristics of molecular and connection settings. Various DNA-based methods developed include PCR, biosensor and CRISPR methods. This review discussed various DNA-based methods, including PCR, biosensor and CRISPR, to detect pork content in food. Among these methods, CRISPR is considered the easiest, fastest and most accurate. Therefore, it is important to develop this method further in the future. In this article, we provide a short review on DNA-based methods for detection of pork content in food products.